(untitled) (Research, Society and Development, 2025)
Peels, seeds and other inedible parts of fruit are wastes products that are frequently discarded during consumption and processing due to a lack of information about their importance. These residues contain considerable amounts of essential nutrients, and their use can bring health benefits, in additional to contributing to the reduction of environmental and economic problems. Since 1970s, several alternatives have been identified with the aim of increasing the use of these residues, either as raw materials for food production or as ingredients that can be incorporated into food. The present study aimed to evaluate the nutritional and minerals composition and identify secondary metabolites of canhú peels (Sclerocarya birrea). The peels were used after the artisanal production of the juice, cleaned and sanitized, dried naturally in the laboratory for 336 hours with ventilation and dried in an oven with air circulation at 65o C for 72 hours. The samples were ground in a processor and sieved to obtain fine particles (flour), followed by laboratory analysis. Parameters such as carbohydrates, crude fiber, proteins and essential minerals showed considerable levels of impact on health and can be used for formulation in other foods.